ASOSIASI CARA PEMBERIAN OBAT DENGAN ONSET DAN DERAJAT KLINIS REAKSI HIPERSENSITIFITAS AKUT/ANAFILAKSIS PADA PENDERITA YANG DIRAWAT DI RSUP SANGLAH DENPASAR BALI - Eka Imbawan, I GN; Suryana, Ketut; Suardamana, Ketut (journal of internal medicine, 2012)
Acute hypersensitivity reaction/anaphylaxis is a post exposure acute reaction involving dermatologic system/mucosal and subcutaneous tissue; while anaphylaxis is an acute systemic reaction involving two or more organ systems (the skin/mucosa and subcutaneous tissue, respiratory system, cardiovascular system, gastrointestinal system). Drugs as allergens can trigger these reactions orally, parenteral, or topically (contact). Different modes of drug administration are known to relate with onset and degree of the resulting clinical features. We conduct a cross sectional study to determine the association between modes of drugs administration with onset and clinical degree in patients hospitalized at Sanglah General Hospital Denpasar. This study involved 205 patients with acute hypersensitivity reactions/anaphylaxis (105 male and 100 female). Mean age was 33.12 (12 ! 80) years, 131 persons (63.9%) were triggered by drugs, while 57 patients (27.8%) were triggered by food, 13 patients (6.3%) by insect sting, and 3 patients (1.5% ) by other allergens. Of 131 patients with drugs as the trigger, 108 patients (82.4%) were given orally, 22 patients (16.8%) were given parenterally and 1 patient (0.8%) was triggered via contact. The mean onset of an acute hypersensitivity reaction/anaphylaxis triggered by oral and parenteral drugs were 4.2 hours and 0.6 hours respectively (p < 0.01). We conclude that modes of drug administration are associated with the onset of symptoms, but not with the degree of clinical manifestation of acute hypersensitivity reaction/anaphylaxi
Keywords: acute hypersensitivity reactions/anaphylaxis, triggering allergen, onset, clinical degrees